2020
DOI: 10.1017/wet.2020.116
|View full text |Cite
|
Sign up to set email alerts
|

Buckhorn plantain (Plantago lanceolata) resistant to 2,4-D in Pennsylvania and alternative control options

Abstract: Buckhorn plantain populations purportedly resistant to 2,4-D were identified in Pennsylvania following long-term, continual applications of the active ingredient in turfgrass systems. The research objectives of this study were to (1) confirm 2,4-D resistance with dose-response experiments, (2) confirm field resistance of buckhorn plantain to 2,4-D in Pennsylvania, and (3) evaluate alternative herbicides for 2,4-D-resistant buckhorn plantain. Greenhouse dose-response experiments evaluated sensitivity of resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, ribwort has demonstrated increased resistance to classical herbicides since 2018. It is therefore important to find new herbicides to control this weed in the near future 6,23 . Common purslane ( P. oleracea ) also is part of the eudicot clade and it primarily infects rice crops 24 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, ribwort has demonstrated increased resistance to classical herbicides since 2018. It is therefore important to find new herbicides to control this weed in the near future 6,23 . Common purslane ( P. oleracea ) also is part of the eudicot clade and it primarily infects rice crops 24 .…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore important to find new herbicides to control this weed in the near future. 6,23 Common purslane (P. oleracea) also is part of the eudicot clade and it primarily infects rice crops. 24 Ryegrass (L. rigidum) is a monocot that mainly affects barley and wheat production, 25 and it also shows resistance phenomena to herbicides such as glyphosate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this population was not cross-resistant to triclopyr, a pyridine carboxylic acid herbicide with an SOA similar to that of 2,4-D. Similarly, Russell et al (2019) identified two buckhorn plantain biotypes resistant to 2,4-D in Pennsylvania that were not resistant to halauxifen-methyl, an arylpicolinate synthetic auxin. Resistance to triclopyr and clopyralid has been confirmed in lawn burweed (Soliva sessilis Ruiz & Pav.)…”
Section: Synthetic Auxin Resistance In Turfgrass (Wssa Group 4)mentioning
confidence: 93%